Fecal IgA Levels and Gut Microbiota Composition Are Regulated by Invariant Natural Killer T Cells. Issue 5 (10th December 2019) - de Aguiar, Cristhiane Favero; Castoldi, Angela; Amano, Mariane T; Ignacio, Aline; Terra, Fernanda Fernandes; Cruz, Mario; Felizardo, Raphael J F; Braga, Tárcio Teodoro; Davanzo, Gustavo Gastão; Gambarini, Victor; Antonio, Tiago; Antiorio, Ana Tada Fonseca Brasil; et al.
Abstract: Background: The gut microbiota is a key element to support host homeostasis and the development of the immune system. The relationship between the microbiota and immunity is a 2-way road, in which the microbiota contributes to the development/function of immune cells and immunity can affect the composition of microbes. In this context, natural killer T cells (NKT cells) are distinct T lymphocytes that play a role in gut immunity and are influenced by gut microbes. In our work, we investigated the involvement of invariant NKT cells (iNKT) in intestinal homeostasis. Results: We found that iNKT-deficient mice (iNKT-KO) had reduced levels of fecal IgA and an altered composition of the gut microbiota, with increased Bacteroidetes . The absence of iNKT cells also affected TGF-β1 levels and plasma cells, which were significantly reduced in knockout (KO) mice. In addition, when submitted to dextran sodium sulfate colitis, iNKT-KO mice had worsening of colitis when compared with wild-type (WT) mice. To further address iNKT cell contribution to intestinal homeostasis, we adoptively transferred iNKT cells to KO mice, and they were submitted to colitis. Transfer of iNKT cells improved colitis and restored fecal IgA levels and gut microbiota. Conclusions: Our results indicate that intestinal NKT cells are important modulators of intestinal homeostasis and that gut microbiota composition may be a potential target in the management of inflammatory bowel diseases. Abstract : Our work demonstrates the important role of invariant natural killer T cells (iNKT cells) as modulators of gut homeostasis. Lack of iNKT cells in knockout mice results in lower levels of fecal IgA and TGF-β1, altered gut microbiota, and increased susceptibility to colitis.